Revisão de Miobantia Giglio-Tos (Mantodea, Thespidae, Miopterynae), com associação molecular de sexos dimórficos e estágios imaturos, e descrição de quatro espécies novas - Araújo, Marcus Vinícius Scherrer de (2013)
The Neotropical praying mantis genus Miobantia Giglio-Tos includes six species with a complex taxonomic history. Although frequently found in the Atlantic Forest, little is known about these species and some obstacles make it difficult identifying these mantids, as the high sexual dimorphism and both sexes known only to one of the six species. This work investigates the taxonomic limits of the species of Miobantia through a cladistic analysis using 99 morphological characters, and sequencing of 700 bp of the mithocondrial gene COI for association of dimorphic sexes and nymphs. An investigation of intraspecific variation is also conducted based on a large number of specimens of M. fuscata (Giglio-Tos) to choose more relevant features for separation of the species to be used in taxonomic comments and identification keys. The male of M. aptera Giglio-Tos, and the females of M. ciliata (Stål) and M. fuscata are described for the first time, and redescription of the males of these and the female of M. aptera are provided based on much complementary data. Miobantianebulosa (Giglio-Tos) is proposed as a junior synonym of M. rustica (Fabr.), based on comparison of the types, including investigation of the male genitalia, and the species is redescribed. Additionally, four new species are here described: M. sp. nov. 1 sp. nov., M. sp. nov. 2 sp. nov., M. sp. nov. 3 sp. nov., and M. sp. nov. 4 sp. nov.; both sexes are described, except only for the male of M. sp. nov. 2. Identification keys are provided for males and females of all valid species, and figures of diagnostic features are provided for all of them. The species distribution is mapped according to literature data and 50 new records